Performance-based contracting in social welfare programs - Heinrich, Carolyn J.; Choi, Youseok (2007)
The Wisconsin Works (W-2) program changed the administrative structure for social welfare services delivery from county government administration to one that includes performance-based contracting and private sector management of programs. We present a theoretical discussion of government contracting and the implications of alternative contract structures for service provider behavior and performance. We then analyze W-2 contract design and management across four contract periods (1997-2005) as the state transitioned to a performance-based contracting regime. We find that the state made rational changes in the W-2 contract specifications and performance measures that should have improved contract efficiency and effectiveness over time, and service providers responded to these changes in allocating effort toward the achievement of priority performance goals. At the same time, deficiencies in program administration and contract management contributed to some contract and performance failures and setbacks. - Reproduced.
Keywords: Social welfare